Fungsi Manajemen Kesiswaan Dalam Peningkatan Kinerja Tenaga Administrasi Sekolah Pada SMP Negeri 12 Kendari - Kaimudin, Hasnani; Sartono, Sartono; Tawai, Adrian (REZ PUBLICA, 2021)
This study aims to determine the application of management functions in the student field in improving the performance of the administrative staff of SMPN 12 Kendari and to determine the performance of the administrative staff of SMPN 12 Kendari in the student field. The method used is descriptive qualitative research method by means of observation, interviews and documentation. The results showed that the student management function in improving the performance of the administrative staff of SMPN 12 Kendari starting from the planning, organizing and mobilizing functions had been carried out well. In the planning function, there is the preparation of student programs, one of which is the admission program for new students, by determining in advance who, when, where to implement it by paying attention to available sources and supported by adequate infrastructure and conducting training and socialization first. Furthermore, the organizing function is to divide the schedule and tasks for each employee. In the function of driving the principal to motivate employees in completing tasks. However, the supervisory function is still not optimal where there is still a lack of employee work discipline. Furthermore, the performance of the administrative staff of SMP Negeri 12 Kendari in terms of quantity and quality is good, where employees pay attention to aspects of accuracy and neatness. However, the punctuality aspect still needs to be improved because there is still a lack of employee work discipline, there are still employees who come late and add work holidays.